2022
DOI: 10.1038/s41419-022-04751-7
|View full text |Cite
|
Sign up to set email alerts
|

Class I HDAC overexpression promotes temozolomide resistance in glioma cells by regulating RAD18 expression

Abstract: Overexpression of histone deacetylases (HDACs) in cancer commonly causes resistance to genotoxic-based therapies. Here, we report on the novel mechanism whereby overexpressed class I HDACs increase the resistance of glioblastoma cells to the SN1 methylating agent temozolomide (TMZ). The chemotherapeutic TMZ triggers the activation of the DNA damage response (DDR) in resistant glioma cells, leading to DNA lesion bypass and cellular survival. Mass spectrometry analysis revealed that the catalytic activity of cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Our study provides paradigms for how ssDNA arises and is remediated by TLS in the unique setting of TMZ-treated GBM. A recent report by Hanisch et al also showed that HDAC-overexpressing gliomas become TMZ-tolerant owing to transcriptional induction of RAD18 56 .…”
Section: Discussionmentioning
confidence: 92%
“…Our study provides paradigms for how ssDNA arises and is remediated by TLS in the unique setting of TMZ-treated GBM. A recent report by Hanisch et al also showed that HDAC-overexpressing gliomas become TMZ-tolerant owing to transcriptional induction of RAD18 56 .…”
Section: Discussionmentioning
confidence: 92%
“…Counterintuitively, increased expression of the genomic protectors RAD18 and MSH2 were negatively associated with overall survival. A possible explanation could be treatment inefficacy at these higher levels of gene expression; both high expression of RAD18 and MSH2 have been correlated to temozolomide resistance in vitro [62,63]. However, a retrospective multicenter study on MSH2 protein expression in high-grade gliomas did not find any association with overall survival when correcting for IDH-mutation status [64].…”
Section: Dna Damage Repair and Genomic Instabilitymentioning
confidence: 99%
“…A recent report by Hanisch et al also showed that HDACoverexpressing gliomas become TMZ-tolerant owing to transcriptional induction of RAD18. 52 Futile MMR of TMZ-induced O 6 mG-thymine mis-pairs activates ATR 53 , signaling a G2 checkpoint that protects from TMZ-induced lethality 54,55 . Here we show coordinate activation of CHK1 and RAD18 in response to TMZ-induced DNA damage, consistent with a common RPA/ssDNA-based activation mechanism for both ATR/CHK1 and RAD18 pathways.…”
Section: Discussionmentioning
confidence: 99%